2020
DOI: 10.1038/s41467-020-18944-1
|View full text |Cite
|
Sign up to set email alerts
|

Rationally designed transition metal hydroxide nanosheet arrays on graphene for artificial CO2 reduction

Abstract: The performance of transition metal hydroxides, as cocatalysts for CO2 photoreduction, is significantly limited by their inherent weaknesses of poor conductivity and stacked structure. Herein, we report the rational assembly of a series of transition metal hydroxides on graphene to act as a cocatalyst ensemble for efficient CO2 photoreduction. In particular, with the Ru-dye as visible light photosensitizer, hierarchical Ni(OH)2 nanosheet arrays-graphene (Ni(OH)2-GR) composites exhibit superior photoactivity an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
126
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 289 publications
(128 citation statements)
references
References 69 publications
2
126
0
Order By: Relevance
“…For the development of efficient photocatalysts, scientists have done a lot of meaningful work. [ 12–14 ] Jiang et al. [ 15 ] reported that by accurately anchoring TiO 2 in two different molecular compartments of MIL‐101, a quantum efficiency of up to 11.3% was achieved, proving that the precise positioning of TiO 2 in the metal‐organic framework (MOF) system can effectively improve the material performance.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For the development of efficient photocatalysts, scientists have done a lot of meaningful work. [ 12–14 ] Jiang et al. [ 15 ] reported that by accurately anchoring TiO 2 in two different molecular compartments of MIL‐101, a quantum efficiency of up to 11.3% was achieved, proving that the precise positioning of TiO 2 in the metal‐organic framework (MOF) system can effectively improve the material performance.…”
Section: Introductionmentioning
confidence: 99%
“…For the development of efficient photocatalysts, scientists have done a lot of meaningful work. [12][13][14] Jiang et al [15] reported that by accurately anchoring TiO 2 in two different molecular compartments of MIL-101, a quantum efficiency of up to 11.3% was achieved, proving that the precise positioning of TiO 2 in the metal-organic framework (MOF) system can effectively improve the material performance. Li et al [16] reported that through a top-down direct metal atomization method to prepare single atoms and the use of CO species to adjust the coordination environment, a high turnover number of 1493.5 could be achieved in CO 2 photoreduction process.…”
mentioning
confidence: 99%
“…Nowadays, direct solar-to-fuel conversion through green photocatalysis technology has received increasing research interests due to its potential for solar energy utilization and storage to relieve the growing energy demands and greenhouse effect (Habisreutinger et al, 2013). With the expansion and deepening of the research, photocatalysis technology has been extended to many fields, such as energy, health, environment, pollution control and value-added chemicals synthesis (Lu et al, 2020). As a result, the relevance of photocatalysis and human life has been increasing steadily.…”
Section: Introduction Photocatalysis Is a Promising Technology For Energy And Environmental Protectionmentioning
confidence: 99%
“…44 Lu et al prepared rationally designed nickel hydroxides nansheets array on graphene by utilizing hydrothermal treatment. 45 The primary disadvantages such as controlling the reaction parameters at high temperature, bulk production, and requirement of conducting substrate limited the application of supercapacitor in numerous fields.…”
Section: Introductionmentioning
confidence: 99%